TRANSPARENT COMPRESSION SCHEME FOR LINUX FILE SYSTEM - Basir, M. A.; Yousaf, M. H. (The Nucleus, 2012)
Data footprint in data centers is growing day by day. Servers being used in research institutions, commercial web hosting companies and other enterprise server environment are now dealing with more and more bytes. Most of these servers have Linux operating systems and Ext2/3 comes as default file system in latest Linux kernel. A high-end compression system could be introduced in Ext2/3. It will be helpful in reducing data footprint in Linux based server environment. With slight modifications and using the sparse block feature of Ext2/3 file system transparent compression could be achieved. The reduced data footprint will result in reduced power consumption due to lesser disk reads and writes, and of course less data traffic on NAS(Network Attached Storage) and SAN(Storage Area Network). The reduced hardware might result in less management cost and of course less space for hardware.